Eating behavior of schizophrenic patients - AGUIAR-BLOEMER, Ana Carolina; AGLIUSSI, Rosina Gabriela; Maehara Pereira PINHO, Thiago; FURTADO, Erikson Felipe; DIEZ-GARCIA, Rosa Wanda (Revista de Nutrição, 2023)
Objective To assess the eating behavior, food practices, nutritional and metabolic profiles of patients with schizophrenia undergoing treatment. Methods Cross-sectional exploratory descriptive qualitative study used a semi-structured questionnaire on the eating behavior, food practices, and perception of changes after the initiation of drug therapy and a quantitative method using anthropometric and body composition measurements, metabolic parameters, and 5-day dietary records to analyze nutrient ingestion of patients with schizophrenia in an outpatient clinic at a tertiary hospital (n=33). The qualitative data were analyzed and coded by three researchers and quantitative data were analyzed using descriptive exploratory statistics. Results The results of this study showed that schizophrenic patients presented high prevalence of excess weight (71.0%), metabolic syndrome (42.0%), dyslipidemia (62.0%), changes in appetite (76.0%), and increase in energy intake (74.2%), associated with important irregularities in eating behavior and food practices (such as irregularity of meals, emotional intake, high carbohydrate and fat intake, and low energy expenditure) and lifestyle (changes in social and work routines). Conclusion This eating profile may interact synergistically with psychotropic drugs to contribute to weight gain and metabolic changes in schizophrenia. Nutrition education may prevent and monitor the risk of metabolic and nutrition problems, irrespective of the medications used.